The Effects of Implementing the Strategy of Semantic Feature Analysis (SFA) in Promoting Vocabulary in School-Aged Portuguese Children in Inclusive Schools - Elisabete Verde; Sílvia Oliveira; Anabela Cruz-Santos; Etelvina Lima (MDPI AG, 2024)
Background: The purpose of this study was to apply and analyze the impact of the semantic feature analysis (SFA) strategy on vocabulary development and comprehension of texts and theoretical concepts in Portuguese school-age students with and without special educational needs (SEN) attending inclusive schools. Method: The research design was quasi-experimental. The SFA was administered in ten sessions of approximately 60 min each. The sample was a convenience sample and consisted of selecting three classes in each school: (i) in the first cycle of basic education, 65 students were divided into a control group, an experimental group and a structured teaching group; (ii) in the second cycle of basic education, 55 students were divided into an experimental group, an online virtual school and a control group. Results: (1) The SFA strategy is motivating, appealing, inexpensive, flexible and easy to implement; (2) learning the SFA strategy is easy and can be successfully taught in any classroom; (3) the performance of the students assigned to the experimental groups was significantly higher in both cycles compared to all the other groups; (4) the effect sizes were 0.87 in the first cycle and 0.88 in the second cycle. Conclusion: The SFA strategy effectively promotes the development of vocabulary, concept knowledge and text comprehension in school-age children, being more effective than regular teaching.